Evaluation of the Synthesis of Zeolite SSZ-13 using Choline Chloride and Different Crystallization Seeds and its Application in the Thermocatalytic Degradation of Ultra-High Molecular Weight Polyethylene - Solano,Julyane R. S. (2021)
Abstract The synthesis of SSZ-13 was studied by evaluating the influence of two types of crystallization seeds with CHA structure (S1 seeds prepared in fluoride medium and S2 seeds by the conversion of zeolite Y), SiO2/Al2O3 (28, 40, 60 and 100) and OH/SiO2 (0.6 and 0.8) ratios. Choline chloride was used as the structure-directing agent and the crystallizations occurred at 140 ºC from 24 to 96 h. S1 seeds led to the coexistence of zeolites SSZ-13 and P, while S2 seeds promoted in all SiO2/Al2O3 ratios and OH/SiO2 = 0.8, the formation of pure SSZ-13 after 24 h. The SSZ-13 samples are formed by clusters of crystals with cuboid-like morphology and exhibited textural properties typical of CHA framework. SSZ-13 zeolite led to a decrease in the temperature and the activation energy required for the degradation of ultra-high molecular weight polyethylene polymer, demonstrating its efficiency as catalyst in this process.